Selous aerial survey 1981 - Borner, Markus (Pachyderm, 1983)
Summarizes results from the 1981 Selous aerial survey, which included about 35% of the Reserve, and compares them to the 1976 data. Elephant numbers seem to have remained relatively stable with the 1976 estimate being 82,628 +/- 17% and the 1981 one being 85,504 +/- 12%. However, the skeleton count increased about 50% with the ratio of dead to live animals rising from 7.8% to 12.3% over the four year period and much of the increase took place close to settled areas. Full report also in file.